Surface Layer Modification of 12Cr1MoV and 30CrMnSiNi2 Steels by Zr+ Ion Beam to Improve the Fatigue Durability. (2015) - Vlasov, Ilya; Panin, Sergey; Sergeev, Viktor; Lyubutin, Pavel; Bogdanov, Oleg; Maruschak, Pavlo; Boris Ovechkin,; Menou, Abdellah
Abstract: With the use of optical/scanning electron microscopy and microindentation some peculiarities of structure modification over cross-section as well as mechanical properties of 12Cr1MoV and 30CrMnSiNi2 steel specimens subjected to ion-arc treatment by Zr ion beam were investigated. It is shown that changing of the microstructure takes place over entire cross-section that is not the case of material softening due to annealing. Within the revealed results on structure modification the data on changing mechanical properties under cyclic and static tension of the irradiated specimens are interpreted. Of particular interest are results on strain measurement by digital image correlation technique.